2004
DOI: 10.1023/b:brea.0000025409.69516.23
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging in Comparison to Clinical Palpation in Assessing the Response of Breast Cancer to Epirubicin Primary Chemotherapy

Abstract: As compared to pathology specimens, MRI is able to represent the extent of cancer more accurately than clinical palpation. It constitutes a promising technique in assessing the BC response to PC. The current limit of MRI is the scarce specificity in predicting the nature of residual disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Nineteen studies were eligible for inclusion in the systematic review (Weatherall et al , 2001; Balu-Maestro et al , 2002; Partridge et al , 2002; Rosen et al , 2003; Bodini et al , 2004; Chen et al , 2004; Londero et al , 2004; Julius et al , 2005; Montemurro et al , Yeh et al , 2005; Akazawa et al , 2006; Bollet et al , 2007; Segara et al , 2007; Bhattacharyya et al , 2008; Moon et al , 2009; Prati et al , 2009; Nakahara et al , 2010; Wright et al , 2010; Guarneri et al , 2011), reporting data on 958 patients undergoing MRI and/or comparator tests; MRI data were reported for 953 patients. Studies enrolled patients between 1998 and 2007 (median mid-point of recruitment 2002), and included a median of 38 patients with MRI data (range 12–195).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nineteen studies were eligible for inclusion in the systematic review (Weatherall et al , 2001; Balu-Maestro et al , 2002; Partridge et al , 2002; Rosen et al , 2003; Bodini et al , 2004; Chen et al , 2004; Londero et al , 2004; Julius et al , 2005; Montemurro et al , Yeh et al , 2005; Akazawa et al , 2006; Bollet et al , 2007; Segara et al , 2007; Bhattacharyya et al , 2008; Moon et al , 2009; Prati et al , 2009; Nakahara et al , 2010; Wright et al , 2010; Guarneri et al , 2011), reporting data on 958 patients undergoing MRI and/or comparator tests; MRI data were reported for 953 patients. Studies enrolled patients between 1998 and 2007 (median mid-point of recruitment 2002), and included a median of 38 patients with MRI data (range 12–195).…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies (Weatherall et al , 2001; Partridge et al , 2002; Rosen et al , 2003; Bodini et al , 2004; Chen et al , 2004; Londero et al , 2004; Montemurro et al , 2005; Akazawa et al , 2006; Bollet et al , 2007; Segara et al , 2007; Bhattacharyya et al , 2008; Moon et al , 2009; Prati et al , 2009; Nakahara et al , 2010; Wright et al , 2010; Guarneri et al , 2011) reported correlations between MRI and pathologic tumour size, and similar correlations for at least one alternative test, either by the Pearson's ( N =9) or Spearman's ( N =5) method (in two studies (Weatherall et al , 2001; Partridge et al , 2002), the method was not specified). The range of correlation coefficients was wide (0.21–0.92), with a median value of 0.70 (Supplementary Informtion Resource 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] The authors cite a number of studies demonstrating the value of MRI in this arena of imaging. MRI has been shown to be more sensitive and more specific (in certain studies) than other imaging modalities, and has been shown to more accurately correlate with post surgical pathology.…”
mentioning
confidence: 99%
“…Although some aspects of palpation can improve with training, 7,8 palpation has been shown to be problematic in the detection of cancer, [9][10][11][12] assessment of joint laxity, 13 determination of fetal position 14 , glaucoma, 15 and in assessing circulatory disorders 3,16 As a specific form of palpation, manual assessment of tissue stiffness fares no better. Judgments made by experienced manipulative physical therapists were found to have poor reliability 17 and tended to underestimate the magnitude of applied force and overestimate tissue motion.…”
mentioning
confidence: 99%